Successful management of recurrent cutaneous granulomas caused by Candida albicans using aminolevulinic acid photodynamic therapy post-surgery: A case report - Lulu Wang; Yahui Feng; Sisi Wang; Leyao Shi; Yong Ren; Zhiya Yang; Dongmei Shi (Photodiagnosis and Photodynamic Therapy)
Photodynamic therapy (PDT) is a treatment that combines a photosensitive drug with light to induce phototoxic response in target cells, primarily through singlet oxygen.. Few cases have reported the combination of PDT with antifungal agents to successfully treat Candida infection. We present a case of cutaneous mass caused by Candida albicans (C.albicans) treated solely with 5-aminolevulinic acid (ALA)- PDT. A 21-year-old female presented with a cutaneous lesion on her right elbow,. characterized by erythema, nodules, and cysts that had persisted for 3 months after surgical excision. The diagnosis of infectious granulomas caused by C. albicans was confirmed through tissue histopathological, morphology and molecular sequence of the isolated pathogen. The lesion was completely resolved after two sessions of ALA-PDT adminstered 9 days apart. During the 6-month follow-up, there were no signs of relapse. This case suggested that mono-ALA-PDT can be an effective treatment option for single lesion on the body surface caused by C. albicans deep infection.